A standardized database management of middle ear surgery in Korea. - Kim H (Acta Oto-Laryngologica (Supplement))
Conclusion. The classification and hearing result reporting system of middle ear surgery provide a set of standard that otologic surgeons should comply with when they investigate the efficacy of procedures or report the post-operative results of middle ear surgery. Keeping up with this system will, in turn, facilitate and activate the evidence-based clinical research they would ask for. Objectives. The aims of the project were to establish the standardized classification nomenclature, to propose a guideline for the post-operative result reporting system, and to develop a database management program for middle ear surgery. Methods. Nine otologic surgeons from seven university hospitals in Korea carried out a field survey on the nation-wide status of middle ear surgery and its records, and also collected the information regarding international classification and result reporting system from 2001 through 2004. To make a consensus, it also underwent a process of public audit and, a questionnaire investigation, as well. Results. The classification of surgery consisted of four kinds of procedures of mastoidectomy, tympanoplasty, extraneous procedures, and concurrent procedures. Post-operative hearing result reporting consisted of basic requirement and reporting guidelines of hearing success. The basic requirements stated minimum follow up duration, and computing formulae of pure tone average (PTA) and post-operative air bone gap (ABG). The reporting guidelines included criteria of hearing success (Post-operative ABG <= 20 dB, hearing gain >=15 dB, or hearing level <=30 dB), post-operative ABG grading of excellent, good, no or poor improvement, and comparisons of hearing improvement among the groups. Next, a database management program was developed using the standardized classification and result reporting system. Structure of database is composed of 144 fields including patient information/preoperative findings (45 fields), operative findings (36 fields), operative procedures (29 fields), and post-operative follow up (23 fields).